If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 24 = 0 Reorder the terms: 24 + -8x = 0 Solving 24 + -8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -8x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -8x = 0 + -24 -8x = 0 + -24 Combine like terms: 0 + -24 = -24 -8x = -24 Divide each side by '-8'. x = 3 Simplifying x = 3
| 25x+5x-15=0 | | 9x-11=4x+6+5x+5 | | 9(m+2)+1=19+9m | | 5t+10=2t+31 | | 2x+4y+7=0 | | 21+2w=p | | 2x-2x+2=0 | | -2-3y=22 | | 5x=21+2a | | -x+4x=0 | | 3v+10=31 | | 4g+9=2g+17 | | Y=(-x)+8 | | -4x-2x-6=0 | | 2x+4=100000 | | 443x+8=11 | | Y=-12x | | -7x+9x+4=0 | | 6+4(3-k)=2(-2k+9) | | 12=3v-15 | | 8p-8=10-3p | | 5-2y=y | | 4x^2-9x+11=2x+5 | | 8x^3+24x-24x^2-8=0 | | 4x^2+24x+8=0 | | 2x^3+3x^2-12x-10=0 | | x^2+10x+39=-5x-5 | | 6k-5k+10-18= | | h^2+10h=21 | | 7t+3t=30 | | 7t+3t=11 | | 5x+39=28 |